Transformational School Leadership from a Neo-Daoist Lens - Zhang, Yenming; Tan, Charlene (Philosophical Inquiry in Education, 2021)
In this article, we aim to extend the existing literature on the theory of transformational school leadership through a neo-Daoist lens. Focussing on the writings of the third-century Chinese philosopher Wang Bi, we make three arguments. First, his ideas promote a transformational leader who effects change through ziran (spontaneity or natural actions). Second, such leaders inspire all of their staff to work towards a communitarian vision by exercising situational judgement and wuming (namelessness). Third, Wang’s philosophy has the potential to address a major criticism concerning the abuse of power in transformational leadership. A neo-Daoist leader does not seek to push for changes in an autocratic, divisive, and hurried manner. Instead, such a leader draws strength from contemplative practice and contextual sensitivity to foster harmonious relationships.